Incorporating rights strategies to advance corporate accountability - George, Erika (Oxford University Press, 2021)
Chinese journalist Shi Tao did not report on the 2008 Olympic Games in Beijing because he was serving a prison sentence for divulging a "state secret." Using his Yahoo! e-mail account, Shi Tao sent a message about restrictions imposed on local journalists to the U.S.-based Asia Democracy Foundation. Chinese authorities tracked him down with the assistance of Hong Kong based Yahoo! Holdings Ltd., a Yahoo! foreign subsidiary that provided China's state security apparatus with details allowing the communications to be traced back to Shi Tao's computer. Privacy rights and free expression advocacy organizations accused the company of complicity in the government's violation of Shi Tao's rights. When challenged by rights activists concerning his corporation's role in the journalist's imprisonment, Jerry Yang, Yahoo's U.S.-based co-founder reportedly claimed his company was simply complying with local laws. Nigerian environmental and human rights activist Ken Saro-Wiwa did not vote in Nigeria's democratic elections that ended years of military rule because he was executed by the ruling military dictatorship in 1995 for engaging in dissent. An ethnic Ogoni, Saro-Wiwa, had campaigned for increased autonomy for his community, a minority group residing in the oil-producing region of the country. He had organized protests against the environmental damage created by the drilling operations of Royal Dutch Shell and other oil companies in his community. Saro-Wiwa was "tried" by a special military court under procedures inconsistent with international fair trial standards, convicted along with the other "Ogoni Nine," and hanged. When criticized for its silence with respect to the Saro-Wiwa's trial, a member of Shell's general management reportedly stated the company was not in a position to question or comment on the country's rules, regulations or procedures. Colombian trade unionist "Pablo Perez 50" did not live to see the Colombian government reach a peace accord with the FARC guerrilla movement and adopt sweeping land restitution to return those forcibly displaced by violence during the country's conflict to their homes. "Pablo Perez 50" worked on a banana plantation that supplied Chiquita Brands International until the evening he was kidnapped and killed by the armed paramilitary organization that provided the company with security. In a settlement of criminal charges with the U.S. Justice Department, Chiquita was fined for violating U.S. anti-terrorism laws for making payments to designated foreign terrorist organizations. Yet, the civil claims of thousands of Colombians who suffered abuses allegedly due to Chiquita's complicit conduct were rejected by a federal court in the United States leaving victims with fewer forums for accessing a judicial remedy. Company representatives maintained there was no choice but to cooperate with paramilitaries given the complicated context of the country's conflict situation"--